ECHIDNA Protein Impacts on Male Fertility in Arabidopsis by Mediating trans-Golgi Network Secretory Trafficking during Anther and Pollen Development . Issue 3 (14th January 2014) - Fan, Xinping; Yang, Caiyun; Klisch, Doris; Ferguson, Alison; Bhaellero, Rishi P.; Niu, Xiwu; Wilson, Zoe A.
Abstract : ECHIDNA-mediated trans-Golgi network trafficking is needed for full male fertility in Arabidopsis and is required for anther and pollen formation, filament elongation, and anther dehiscence in addition to pollen tube formation . Abstract: The trans-Golgi network (TGN ) plays a central role in cellular secretion and has been implicated in sorting cargo destined for the plasma membrane. Previously, the Arabidopsis ( Arabidopsis thaliana ) echidna ( ech ) mutant was shown to exhibit a dwarf phenotype due to impaired cell expansion. However, ech also has a previously uncharacterized phenotype of reduced male fertility. This semisterility is due to decreased anther size and reduced amounts of pollen but also to decreased pollen viability, impaired anther opening, and pollen tube growth. An ECH translational fusion (ECHPro:ECH-YELLOW FLUORESCENT PROTEIN) revealed developmentally regulated tissue-specific expression, with expression in the tapetum during early anther development and microspore release and subsequent expression in the pollen, pollen tube, and stylar tissues. Pollen viability and production, along with germination and pollen tube growth, were all impaired. The ech anther endothecium secondary wall thickening also appeared reduced and disorganized, resulting in incomplete anther opening. This did not appear to be due to anther secondary thickening regulatory genes but perhaps to altered secretion of wall materials through the TGN as a consequence of the absence of the ECH protein. ECH expression is critical for a variety of aspects of male reproduction, including the production of functional pollen grains, their effective release, germination, and tube formation. These stages of pollen development are fundamentally influenced by TGN trafficking of hormones and wall components. Overall, this suggests that the fertility defect is multifaceted, with the TGN trafficking playing a significant role in the process of both pollen formation and subsequent fertilization.